2018
DOI: 10.1080/20008198.2018.1478583
|View full text |Cite
|
Sign up to set email alerts
|

The Parent Trauma Response Questionnaire (PTRQ): development and preliminary validation

Abstract: Background: Following a child’s experience of trauma, parental response is thought to play an important role in either facilitating or hindering their psychological adjustment. However, the ability to investigate the role of parenting responses in the post-trauma period has been hampered by a lack of valid and reliable measures. Objectives: The aim of this study was to design, and provide a preliminary validation of, the Parent Trauma Response Questionnaire (PTRQ), a self-report measure of parental appraisals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…School‐aged children are likely to be dependent on their parents to determine the extent of their engagement with, versus avoidance of, trauma reminders. Our results add to the growing literature suggesting parents can actively influence how children cope following a traumatic experience (Cobham et al., ; Marsac et al., ; Williamson, Creswell et al., ; Williamson, Hiller et al., ), and suggest that parental involvement in relation to direct exposure to trauma cues may be particularly important. Consistent with such an interpretation, we found tentative support for the possibility that parent promotion of maladaptive coping influences later child PTSS via children's own adoption of maladaptive coping strategies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…School‐aged children are likely to be dependent on their parents to determine the extent of their engagement with, versus avoidance of, trauma reminders. Our results add to the growing literature suggesting parents can actively influence how children cope following a traumatic experience (Cobham et al., ; Marsac et al., ; Williamson, Creswell et al., ; Williamson, Hiller et al., ), and suggest that parental involvement in relation to direct exposure to trauma cues may be particularly important. Consistent with such an interpretation, we found tentative support for the possibility that parent promotion of maladaptive coping influences later child PTSS via children's own adoption of maladaptive coping strategies.…”
Section: Discussionsupporting
confidence: 74%
“…Parents completed the Parental Trauma Response Questionnaire (PTRQ), a self‐report measure of their appraisals relating to the child's trauma and their provision of trauma‐specific support to the child (Williamson, Hiller et al., ). The 30‐item appraisal scale comprises three subscales: (a) permanent change/damage to the child or family, (b) preoccupation with the child's vulnerability, and (c) self‐directed blame, rated on a scale ranging from 0 = don't agree at all to 3 = completely agree .…”
Section: Methodsmentioning
confidence: 99%
“…Highly related to parental emotion socialization, previous studies have identified that parental availability to discuss stressors may mitigate the negative effects of stress-exposure on children’s symptomatology (Carpenter et al, 2017 ; Stallard et al, 2001 ). Parents who provide opportunities for children to engage in discussions about their reactions to stressful events may be able to prevent children’s development of symptomatology by helping children to reframe negative appraisals of stressful events and to co-create a narrative about a stressor (Goodman et al, 1997 ; Williamson et al, 2018 ). Relatedly, parental discussion of stressful events with children has been proposed as one mechanism by which parents may be able to affect the content of children’s narratives about stress exposure (Fivush et al, 2003 ), ultimately buffering the potentially harmful effects of exposure to stress on children’s development of symptomatology (Kilmer and Gil‐Rivas, 2010 ).…”
Section: Parental Availability For Discussion Of Stressful Eventsmentioning
confidence: 99%
“…Parental maintenance of family routines and practices following children’s exposure to stress is associated with reduced child symptomatology (Boyce, 1981 ; Foy, 1992 ). More broadly, familial commitment to routines has been found to buffer the psychological effects of exposure to trauma (Greeff & Wentworth, 2009 ) and has therefore been hypothesized to be a key family-level mechanism by which parents can promote children’s resilience following stress exposure (Williamson et al, 2018 ).…”
Section: Parental Maintenance Of Family Routines and Practicesmentioning
confidence: 99%
“…Using objects as tools to enable difficult conversations is a technique common to work with children, 24 adults after trauma 25 and with vulnerable adults. 26 The potential of a co-produced questionnaire to act as a conversation catalyst was the basis for this study and the findings confirmed this premise.…”
Section: Discussionmentioning
confidence: 99%